Preparation method and application of Cu / Cu2S / Ti3C2 composite material

Through the photocatalytic reduction technology of Cu/Cu2S/Ti3C2 composite materials, the problem of removing polyvalent radioactive iodine is solved, efficient removal and copper utilization are achieved, and the selection and reuse problems of traditional methods are solved.

CN119281354APending Publication Date: 2025-01-10HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411301046.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art is difficult to synchronously and efficiently remove polyvalent radioactive iodine released in the environment, especially high-valent iodine. Traditional physical adsorbent materials have low selectivity and are easy to degrade, copper-based materials have oxidation and inactivation, and heavy metal toxicity and cost of chemical precipitation. , it is difficult to actually apply to the removal of full-valent iodine.

Method used

Cu/Cu2S/Ti3C2 composite material is used to reduce high-valent iodine to low-valent state under light conditions through photocatalytic reduction technology, and then use Cu to adsorb low-valent iodine in dark environments to achieve efficient removal of multivalent iodine. This material is prepared by hydrothermal reaction, using the combination of Ti3C2 nanosheets and Cu/Cu2S to inhibit Cu oxidation and corrosion, and improve copper utilization and adsorption performance.

Benefits of technology

The efficient removal of multivalent iodine is achieved, the copper utilization and adsorption performance is improved, the reuse defects of traditional methods are improved, and the removal performance of full valent radioactive iodine is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281354A_ABST
    Figure CN119281354A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sewage purification treatment in environmental protection, and discloses a preparation method and application of a Cu / Cu2S / Ti3C2 composite material, and the preparation method comprises the following steps: preparing a copper nitrate solution by using an ethanol / water mixed solution, adding formic acid into the copper nitrate solution, dropwise adding ammonia water, carrying out hydrothermal reaction, cooling, filtering and separating, washing and drying to obtain Cu / Cu2O; dispersing the Cu / Cu2O in a mixed solution of ethanol / water, adding thiourea, carrying out hydrothermal reaction, cooling, centrifuging and drying to obtain Cu / Cu2S; the preparation method comprises the following steps: adding Cu / Cu2S into an ethanol / water mixed solution, uniformly stirring, adding the Ti3C2 nanosheet, and carrying out ultrasonic dispersion, hydrothermal reaction, cooling, filtration separation, washing and drying to obtain the Cu / Cu2S / Ti3C2 composite material. According to the method, multivalent iodine can be effectively removed, and the copper utilization rate is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sewage purification in environmental protection, and in particular to a preparation method of a Cu / Cu2S / Ti3C2 composite material and its application in adsorbing multivalent iodine. Background Art

[0002] Affected by the volatility and intermittency of new energy sources (such as wind power, solar energy, etc.), nuclear power is the base load power source of China's "zero-carbon" energy system. However, the resulting radioactive pollution poses a great threat to human health and the environment. Radioactive iodine is an inevitable product of nuclear fission. In addition to nuclear accidents, spent fuel reprocessing, medical radiotherapy, nuclear testing, etc. are also easily released into the ecological environment. The types and valence states of radioactive iodine are relatively rich (such as I − , I2, IO− 3, etc.), which are easily converted into each other in the environment. Therefore, it is necessary to simultaneously and efficiently remove the radioactive multivalent iodine released into the environment.

[0003] For single-valent radioactive iodine (mainly I − There are many reports on the removal of radioactive iodine (I2), which can be divided into physical adsorption and chemical precipitation. However, there are basically no reports on the simultaneous and efficient removal of all valence states of iodine, especially high-valence states of iodine (HIO, IO− 3). Because the molecular sizes of various forms of iodine are inconsistent, and the pores of traditional physical adsorption materials (such as activated carbon and zeolite molecular sieves) are generally 10~30 Å, their selective adsorption efficiency for radioactive iodine is low in the actual environment where interfering ions exist. The constructed covalent organic framework materials, porous organic polymers, metal-organic framework materials and other new organic porous materials have a pore size distribution that matches the target valence state of iodine and contain electron-rich heterocycles such as N and S. Although they can efficiently and selectively adsorb I − or I2, but the removal capacity of other valence states of iodine is insufficient, and it is easily degraded and inactivated by high-energy irradiation. Therefore, traditional physical adsorption is difficult to be actually applied to the simultaneous and efficient removal of all-valence states of radioactive iodine.

[0004] The chemical precipitation method uses metal ions and part of the valent iodine to form insoluble compounds to achieve effective removal of iodine, such as AgI, AgIO3, Hg2I2, Hg2(IO3)2, PbI2, CuI, etc., which has the advantages of high selectivity and removal efficiency. Affected by the toxicity of heavy metals Hg and Pb and the cost of precious metal Ag, copper is the most promising material in the practical application of radioactive iodine removal. However, copper-based materials are easily inactivated by the formation of a dense CuO layer on the surface, which has long hindered their application in iodine removal. The team of Professor Zhang Guanghui of Tianjin University inhibited the surface oxidation of CuCl by adding a deoxidizer (Na2SO3), significantly improving its adsorption performance. Therefore, solving the problem of oxidation and deactivation of the surface layer of copper-based materials is a prerequisite for its practical application in radioactive iodine removal.

[0005] Considering the application prospects such as reaction conditions, cost-effectiveness, safety and stability, and green and low-carbon, it is a rational choice to use photocatalytic reduction to replace traditional chemical reduction. Photocatalytic reduction technology is also called photoelectrochemical cathodic protection technology in the field of shipbuilding and shipping. It uses light energy to transfer electrons in the valence band (VB) of the anode semiconductor to the conduction band (CB), and then transfers them to the surface of the target metal, causing the metal corrosion potential to shift negatively, thereby inhibiting the metal's oxidative corrosion. Metal sulfides, whose VB is occupied by the S 3p orbital, are higher than the O2p orbital, and form a smaller VB and negative CB value. Because they have a narrower band gap, they show the potential for more efficient use of visible light and stronger reduction ability. However, since the solubility products of common metal sulfide semiconductor materials (ZnS, MnS, CdS, SnS2, In2S3, MoS2, etc.) are much larger than Cu2S, sulfur in other metal sulfides except Cu2S preferentially precipitates with iodine and copper, thereby inhibiting the effective removal of iodine. Therefore, by controlling the valence state of copper in the composite material and the high-valent iodine in the system through photocatalytic technology, it is expected to solve the problem of the difficulty in simultaneously and efficiently removing fully valent radioactive iodine. Summary of the invention

[0006] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a preparation method and application of a Cu / Cu2S / Ti3C2 composite material, which utilizes the photocatalytic reduction performance of Cu / Cu2S / Ti3C2. Under light conditions, Cu2S / Ti3C2 generates photoinduced electrons to inhibit the oxidation corrosion of Cu, and reduces the high-valent iodine in the environment to low-valent iodine. Then, under a dark environment, Cu is used to adsorb low-valent iodine, thereby achieving efficient removal of multivalent iodine. The present invention improves the copper utilization rate and the adsorption performance of multivalent iodine, and provides a technical reference for the removal of radioactive multivalent iodine in wastewater.

[0007] Technical solution: On the one hand, the present invention provides a method for preparing a Cu / Cu2S / Ti3C2 composite material, comprising the following steps: S1: Preparation of Ti3C2 nanosheets; S2: preparing a copper nitrate solution with a mixed solution of C2H5OH-H2O; adding formic acid to the copper nitrate solution, and then adding ammonia water drop by drop, mixing evenly, performing a hydrothermal reaction, cooling, filtering and separating, washing, and drying to obtain Cu / Cu2O; S3: dispersing the Cu / Cu2O in a mixed solution of ethanol / water, adding thiourea, mixing evenly, performing hydrothermal reaction, cooling, centrifuging, and drying to obtain Cu / Cu2S; S4: adding Cu / Cu2S to a mixed solution of C2H5OH-H2O, stirring evenly, adding the Ti3C2 nanosheets, ultrasonically dispersing, hydrothermally reacting, cooling, filtering and separating, washing, and drying to obtain a Cu / Cu2S / Ti3C2 composite material.

[0008] Furthermore, in S1, the specific preparation steps of the Ti3C2 nanosheets are as follows: LiF is completely dissolved in a hydrochloric acid solution, Ti3AlC2 powder is added while stirring, ultrasonic dispersion is performed evenly, the reaction is stirred in an oil bath, centrifugal filtration is performed, and the filter residue is washed; then the filter residue is dispersed in deionized water, nitrogen is blown, low-temperature treatment is performed, ultrasonication is performed, centrifugation is performed, the supernatant is taken, and drying is performed to obtain Ti3C2 nanosheets.

[0009] Furthermore, the mass ratio of the Ti3AlC2 powder, LiF and hydrochloric acid solution is 1:1~2.5:25~60.

[0010] Furthermore, the specific conditions of the oil bath stirring reaction are: reaction temperature 25 ~ 50 ° C, reaction time 18 ~ 36 h; The specific steps of the low-temperature treatment are: placing in an ice bath for 1 hour, and then placing at an ultra-low temperature of −75°C for 1 hour; repeating the above operation 4-5 times, and finally performing ultrasonic treatment in an ice bath for 1 hour.

[0011] Further, in S2, the mass ratio of formic acid, C2H5OH, H2O, copper nitrate and ammonia water is 1:7~18:4~10:0.5~1.5:1~5; In S2, the specific conditions of the hydrothermal reaction are: reaction temperature is 120 ~ 180 ° C, and reaction time is 1.5 ~ 3h.

[0012] Further, in S3, the mass ratio of Cu / Cu2O, thiourea, ethanol and water is 1:0.2-0.8:14-36:8-20; In S3, the specific conditions of the hydrothermal reaction are: reaction temperature is 160-200°C, and reaction time is 18-36h.

[0013] Further, in S4, the mass ratio of the Ti3C2 nanosheets, Cu / Cu2S, C2H5OH and H2O is 1:8~15:140~360:80~200; In S4, the specific conditions of the hydrothermal reaction are: reaction temperature is 160-200°C, and reaction time is 18-36h.

[0014] On the other hand, the present invention provides an application of a Cu / Cu2S / Ti3C2 composite material prepared by any of the methods described above in the adsorption of polyvalent iodine, wherein the Cu / Cu2S / Ti3C2 composite material is put into a water body containing polyvalent iodine to be adsorbed, exposed to light for a period of time, and then adsorbed in the dark.

[0015] Furthermore, the Cu / Cu2S / Ti3C2 composite material after dark adsorption is dried, dispersed in deionized water, illuminated for 2-3 hours, centrifuged, filtered, washed, and dried, and can be used again for multivalent iodine adsorption.

[0016] Furthermore, the amount of the Cu / Cu2S / Ti3C2 composite material added to the water body is 0.25~2g·L -1 ; The illumination time is 1 to 2 h; The dark adsorption time is 2 to 12 h.

[0017] Beneficial effect: The present invention converts Cu / Cu2O into Cu / Cu2S, and then utilizes the negative charge on the surface of Ti3C2 nanosheets (formed after etching Al in Ti3AlC2) to adsorb Cu in Cu / Cu2S. + , under pressure, Cu / Cu2S and Ti3C2 were compounded to prepare Cu / Cu2S / Ti3C2 composite materials, which introduced photocatalytic technology into traditional inexpensive copper-based adsorption materials. (1) Using photoelectrochemical cathode protection technology, under light conditions, the photocatalytic reduction performance of Cu / Cu2S / Ti3C2 was used to generate photoelectrons, thereby inhibiting the oxidation corrosion of the copper surface and ensuring the stable existence of elemental copper; (2) Under visible light, through photocatalytic reduction technology, the photocatalytic reduction performance of Cu / Cu2S / Ti3C2 was used to generate photoelectrons to photocatalytically reduce high-valent iodine (IO− 3, HIO, I2, etc.) to a single low-valent iodine (I − ); (3) In a dark environment, elemental copper efficiently adsorbs low-valent iodine through redox reactions; (4) Under the synergistic effect of light and heating, the thermal precipitation of iodine in the adsorbed material and the photocatalytic regeneration of the adsorption material (copper reduction and iodine release) are promoted, which stimulates the recycling and regeneration function of the photocatalytic adsorption material, improves the defect of the traditional chemical precipitation method that is difficult to reuse, and enhances the removal performance of copper for fully valent radioactive iodine.

[0018] Compared with the prior art, the present invention has the following significant advantages: (1) the present method can prepare a Cu / Cu2S / Ti3C2 composite material in which cubic Cu / Cu2S material is loaded on Ti3C2 nanosheets; (2) the Cu / Cu2S / Ti3C2 composite material prepared by the present method has the characteristics of photocatalytic reduction and iodine adsorption; (3) the Cu / Cu2S in the Cu / Cu2S / Ti3C2 composite material prepared by the present method is a cubic hollow structure, so that the copper in the center that is not easy to participate in the reaction can be removed during use, thereby increasing the copper utilization rate; (4) the defect of the traditional chemical precipitation method that it is difficult to reuse is improved. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 is a SEM image of the Cu / Cu2S / Ti3C2 composite material prepared in embodiment 1; Figure 2 TEM image of the Cu / Cu2S / Ti3C2 composite material prepared in embodiment 1; Figure 3 XRD spectrum of the Cu / Cu2S / Ti3C2 composite material prepared in Implementation Example 1; Figure 4 is an adsorption curve diagram of the Cu / Cu2S / Ti3C2 composite material prepared in embodiment 1; Figure 5 is a SEM image of the Cu / Cu2S / Ti3C2 composite material prepared in embodiment 2; Figure 6 XRD spectrum of the Cu / Cu2S / Ti3C2 composite material prepared in Implementation Method 2; Figure 7 is an adsorption curve diagram of the Cu / Cu2S / Ti3C2 composite material prepared in embodiment 2; Figure 8 is a SEM image of the Cu / Cu2S / Ti3C2 composite material prepared in Embodiment 3; Fig. 9 This is the XRD spectrum of the Cu / Cu2S / Ti3C2 composite material prepared in Implementation Example 3. DETAILED DESCRIPTION

[0020] The present invention is described in detail below in conjunction with the embodiments.

[0021] Implementation 1: 0.8 g LiF was dissolved in 20 mL 36%~38% hydrochloric acid solution, and then 0.5 g Ti3AlC2 powder was added while stirring, ultrasonically dispersed for 10 min, and stirred in an oil bath at 35°C for 24 h to obtain a suspension; centrifuged and filtered, and the filter residue was washed with deionized water until the pH was greater than or equal to 6; then, the filter residue was dispersed in deionized water again, nitrogen was blown for 10 min, placed at 4°C for 1 h, and then placed in an ultra-low temperature refrigerator at −75°C for 1 h to prevent precipitation. The above operation was repeated 5 times; finally, the sample was ultrasonically treated in an ice bath for 1 h, centrifuged at 3500 r / min for 1 h, and the supernatant was vacuum freeze-dried to finally obtain Ti3C2 nanosheets.

[0022] 40 mL of 0.25 M copper nitrate solution was prepared using a mixed solution of C2H5OH-H2O, in which the volume ratio of C2H5OH to H2O was 23:13. 2 mL of formic acid was added to the copper nitrate solution, and after magnetic stirring for 10 min, 4.0 mL of ammonia solution was added dropwise. After magnetic stirring for 10 min, the mixed solution was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor and filled with 80% of the volume of the hydrothermal reactor. Subsequently, the reactor was heated at 150°C for 2 h, and after the reactor was cooled to room temperature, it was filtered and separated, and then washed with deionized water and anhydrous ethanol, and then placed in a vacuum drying oven at 60°C for 10 h to obtain Cu / Cu2O.

[0023] 1 g of the above-mentioned Cu / Cu2O was dispersed in a mixed solution of 40 mL of ethanol / water (volume ratio of 23:13), 0.5 g of thiourea was added, and magnetic stirring was performed for 30 min. The mixture was then transferred to a hydrothermal reactor and reacted at 180°C for 24 h. After cooling to room temperature, the mixture was centrifugally filtered and vacuum freeze-dried to finally obtain Cu / Cu2S.

[0024] 1 g of the above-mentioned Cu / Cu2S was added to 40 mL of a mixed solution of C2H5OH-H2O (volume ratio of 23:13), and after stirring evenly, 0.1 g of Ti3C2 nanosheets was added to the above solution and ultrasonically dispersed. The mixed solution was transferred to a polytetrafluoroethylene liner of a hydrothermal reactor and reacted at 180°C for 24 h. After the reaction, the reactor was cooled to room temperature, filtered and separated, and then washed with deionized water and anhydrous ethanol, and vacuum freeze-dried to finally obtain a Cu / Cu2S / Ti3C2 composite material.

[0025] The morphology of the Cu / Cu2S / Ti3C2 composite material prepared in this embodiment was observed by SEM ( Figure 1 ), indicating that the prepared Cu / Cu2S material is loaded on the Ti3C2 nanosheets. TEM of Cu / Cu2S / Ti3C2 composite material ( Figure 2) indicates that the prepared Cu / Cu2S is a cubic hollow structure. Figure 3 This is the XRD spectrum of the Cu / Cu2S / Ti3C2 composite material prepared in this embodiment. Due to the low content of Ti3C2, the peak of Ti3C2 cannot be seen.

[0026] 50 mg of the Cu / Cu2S / Ti3C2 composite material prepared above was added to 50 mL of a solution containing 0.1 mM I2 (10% methanol solution) and 0.20 mM iodide ions. After irradiation at room temperature for 2 h, it was darkly adsorbed at room temperature, and the residual iodine concentration in the solution was measured by ICP. Figure 4 The adsorption results showed that the Cu / Cu2S / Ti3C2 composite material reached adsorption equilibrium within 60 min, and the adsorption efficiency reached 98.98%.

[0027] Take 40 mg of the dried product after adsorption of polyvalent iodine and disperse it in deionized water. After irradiation at room temperature for 2 h, centrifuge, filter and separate, wash with deionized water and anhydrous ethanol, and freeze-dry in vacuum to obtain a reactivated Cu / Cu2S / Ti3C2 composite material, which can be used again for polyvalent iodine adsorption.

[0028] 20 mg of the reactivated Cu / Cu2S / Ti3C2 composite material was added to 20 mL of a solution containing 0.1 mM I2 (10% methanol solution) and 0.20 mM iodine ions, and then adsorbed in the dark at room temperature for 2 hours. The residual iodine concentration in the solution was measured by ICP. The adsorption efficiency of the Cu / Cu2S / Ti3C2 composite material can still reach 86.32%.

[0029] Implementation 2: 0.5 g LiF was dissolved in 12.5 mL 36%~38% hydrochloric acid solution, and then 0.5 g Ti3AlC2 powder was added while stirring, ultrasonically dispersed for 10 min, and stirred in an oil bath at 25°C for 18 h to obtain a suspension. Centrifugal filtration was performed, and the filter residue was washed with deionized water until the pH was greater than or equal to 6. Subsequently, the filter residue was dispersed in deionized water, nitrogen was blown for 10 min, placed at 4°C for 1 h, and then placed in an ultra-low temperature refrigerator at -75°C for 1 h to prevent precipitation. The above operation was repeated 5 times. Finally, the sample was ultrasonically treated in an ice bath for 1 h, centrifuged at 3000 r / min for 1.5 h, and the supernatant was vacuum freeze-dried to finally obtain Ti3C2 nanosheets.

[0030] 20 mL of 0.25 M copper nitrate solution was prepared using a mixed solution of C2H5OH-H2O, in which the volume ratio of C2H5OH to H2O was 23:13. 2 mL of formic acid was added to the copper nitrate solution, and after magnetic stirring for 10 min, 2.0 mL of ammonia solution was added dropwise. After magnetic stirring for 10 min, the mixed solution was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor, filling 80% of the volume of the hydrothermal reactor. Subsequently, the reactor was heated at 120 ºC for 3 h, and the reactor was cooled to room temperature, filtered and separated, and then washed with deionized water and anhydrous ethanol, and then placed in a vacuum drying oven at 60 ºC for 10 h to obtain Cu / Cu2O.

[0031] 1 g of the above-mentioned Cu / Cu2O was dispersed in a mixed solution of 22 mL of ethanol / water (volume ratio of 23:13), 0.2 g of thiourea was added, and magnetic stirring was performed for 30 min. The mixture was then transferred to a hydrothermal reactor and reacted at 160°C for 36 h. After cooling to room temperature, the mixture was centrifugally filtered and vacuum freeze-dried to finally obtain Cu / Cu2S.

[0032] 0.8 g of the above-mentioned Cu / Cu2S was added to a mixed solution of 22 mL C2H5OH-H2O (volume ratio of 23:13), and after stirring evenly, 0.1 g of Ti3C2 nanosheets was added to the above solution, ultrasonically dispersed, and the mixed solution was transferred to the polytetrafluoro liner of a hydrothermal reactor and reacted at 160°C for 36 h. After the reaction, the reactor was cooled to room temperature, filtered and separated, and then washed with deionized water and anhydrous ethanol, and vacuum freeze-dried to finally obtain a Cu / Cu2S / Ti3C2 composite material.

[0033] The morphology of the Cu / Cu2S / Ti3C2 composite material prepared in this embodiment was observed by SEM ( Figure 5 ), indicating that the prepared cubic Cu / Cu2S material is loaded on Ti3C2 nanosheets. Figure 6 This is the XRD spectrum of the Cu / Cu2S / Ti3C2 composite material prepared in this embodiment. Due to the low content of Ti3C2, the peak of Ti3C2 cannot be seen.

[0034] 50 mg of the Cu / Cu2S / Ti3C2 composite material prepared above was added to 25 mL of a solution containing 0.2 mM iodide ions and 0.10 mM iodate ions, and after irradiation at 35°C for 1 h, dark adsorption was performed, and the residual iodine concentration in the solution was measured by ICP. Figure 7 The adsorption results showed that the Cu / Cu2S / Ti3C2 composite material reached adsorption equilibrium within 2 h, and the adsorption efficiency reached 95.64%.

[0035] Implementation 3: 1.25 g LiF was dissolved in 30 mL 36%~38% hydrochloric acid solution, and then 0.5 g Ti3AlC2 powder was added while stirring, ultrasonically dispersed for 10 min, stirred in an oil bath at 50°C for 36 h, and a suspension was obtained. The suspension was centrifuged and filtered, and the residue was washed with deionized water until the pH was greater than or equal to 6. Subsequently, the residue was dispersed in deionized water, nitrogen was blown for 10 min, placed at 4°C for 1 h, and then placed in an ultra-low temperature refrigerator at -75°C for 1 h to prevent precipitation. The above operation was repeated 5 times. Finally, the sample was ultrasonically treated in an ice bath for 1 h, centrifuged at 4000 r / min for 40 min, and the supernatant was vacuum freeze-dried to finally obtain Ti3C2 nanosheets.

[0036] 56 mL of 0.25 M copper nitrate solution was prepared using a mixed solution of C2H5OH-H2O, in which the volume ratio of C2H5OH to H2O was 23:13. 2 mL of formic acid was added to the above copper nitrate solution, and after magnetic stirring for 10 min, 10.0 mL of ammonia solution was added dropwise. After magnetic stirring for 10 min, the mixed solution was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor and filled with 80% of the volume of the hydrothermal reactor. Subsequently, the reactor was heated at 180°C for 1.5 h, and the reactor was cooled to room temperature, filtered and separated, and then washed with deionized water and anhydrous ethanol, and then placed in a vacuum drying oven at 60°C for 10 h to obtain Cu / Cu2O.

[0037] 1 g of the above Cu / Cu2O was dispersed in 56 mL of a mixed solution of ethanol / water (volume ratio of 23:13), 0.8 g of thiourea was added, and magnetic stirring was performed for 30 min. The mixture was then transferred to a hydrothermal reactor and reacted at 200°C for 18 h. After cooling to room temperature, the mixture was centrifugally filtered and vacuum freeze-dried to finally obtain Cu / Cu2S.

[0038] 1.5 g of the above-mentioned Cu / Cu2S was added to 56 mL of a mixed solution of C2H5OH-H2O (volume ratio of 23:13), and after stirring evenly, 0.1 g of Ti3C2 nanosheets was added to the above solution and ultrasonically dispersed. The mixed solution was transferred to a polytetrafluoroethylene liner of a hydrothermal reactor and reacted at 200°C for 18 h. After the reaction, the reactor was cooled to room temperature, filtered and separated, and then washed with deionized water and anhydrous ethanol, and vacuum freeze-dried to finally obtain a Cu / Cu2S / Ti3C2 composite material.

[0039] The morphology of the Cu / Cu2S / Ti3C2 composite material prepared in this embodiment was observed by SEM ( Figure 8 ), indicating that the prepared cubic Cu / Cu2S material is loaded on Ti3C2 nanosheets. Fig. 9This is the XRD spectrum of the Cu / Cu2S / Ti3C2 composite material prepared in this embodiment. Due to the low content of Ti3C2, the peak of Ti3C2 cannot be seen.

[0040] 25 mg of the Cu / Cu2S / Ti3C2 composite material prepared above was added to 100 mL of a solution containing 0.1 mM iodate, 0.1 mM I2 (10% methanol solution) and 0.10 mM iodide ion, and then illuminated at 55°C for 2 h and then adsorbed in the dark to adsorb multivalent iodine in the water.

[0041] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a Cu / Cu2S / Ti3C2 composite material, characterized in that: The following steps are involved: S1: Preparation of Ti3C2 nanosheets; S2: preparing a copper nitrate solution with a mixed solution of C2H5OH-H2O; adding formic acid to the copper nitrate solution, and then adding ammonia water drop by drop, mixing evenly, performing a hydrothermal reaction, cooling, filtering and separating, washing, and drying to obtain Cu / Cu2O; S3: dispersing the Cu / Cu2O in a mixed solution of ethanol / water, adding thiourea, mixing evenly, performing hydrothermal reaction, cooling, centrifuging, and drying to obtain Cu / Cu2S; S4: adding Cu / Cu2S to a mixed solution of C2H5OH-H2O, stirring evenly, adding the Ti3C2 nanosheets, ultrasonically dispersing, hydrothermally reacting, cooling, filtering and separating, washing, and drying to obtain a Cu / Cu2S / Ti3C2 composite material.

2. The method for preparing the Cu / Cu2S / Ti3C2 composite material according to claim 1, characterized in that: In S1, the specific preparation steps of the Ti3C2 nanosheets are as follows: LiF is completely dissolved in a hydrochloric acid solution, Ti3AlC2 powder is added while stirring, ultrasonic dispersion is performed evenly, the reaction is stirred in an oil bath, centrifugal filtration is performed, and the filter residue is washed; then the filter residue is dispersed in deionized water, nitrogen is blown, low-temperature treatment is performed, ultrasonication is performed, centrifugation is performed, the supernatant is taken, and drying is performed to obtain Ti3C2 nanosheets.

3. The method for preparing the Cu / Cu2S / Ti3C2 composite material according to claim 2, characterized in that: The mass ratio of the Ti3AlC2 powder, LiF and hydrochloric acid solution is 1:1-2.5:25-60.

4. The method for preparing the Cu / Cu2S / Ti3C2 composite material according to claim 2, characterized in that: The specific conditions of the oil bath stirring reaction are: reaction temperature 25 ~ 50 ° C, reaction time 18 ~ 36 h; The specific steps of the low-temperature treatment are: placing in an ice bath for 1 hour, and then placing at an ultra-low temperature of −75°C for 1 hour; repeating the above operation 4-5 times, and finally performing ultrasonic treatment in an ice bath for 1 hour.

5. The method for preparing the Cu / Cu2S / Ti3C2 composite material according to claim 1, characterized in that: In S2, the mass ratio of formic acid, C2H5OH, H2O, copper nitrate and ammonia water is 1:7-18:4-10:0.5-1.5:1-5; In S2, the specific conditions of the hydrothermal reaction are: reaction temperature is 120 ~ 180 ° C, and reaction time is 1.5 ~ 3 h.

6. The method for preparing the Cu / Cu2S / Ti3C2 composite material according to claim 1, characterized in that: In S3, the mass ratio of Cu / Cu2O, thiourea, ethanol and water is 1:0.2-0.8:14-36:8-20; In S3, the specific conditions of the hydrothermal reaction are: reaction temperature is 160-200°C, and reaction time is 18-36 h.

7. The method for preparing the Cu / Cu2S / Ti3C2 composite material according to claim 1, characterized in that: In S4, the mass ratio of the Ti3C2 nanosheets, Cu / Cu2S, C2H5OH and H2O is 1:8-15:140-360:80-200; In S4, the specific conditions of the hydrothermal reaction are: reaction temperature is 160-200°C, and reaction time is 18-36 h.

8. Use of a Cu / Cu2S / Ti3C2 composite material prepared by the method according to any one of claims 1 to 7 in the adsorption of multivalent iodine, characterized in that: The Cu / Cu2S / Ti3C2 composite material is put into a water body containing multivalent iodine to be adsorbed, illuminated for a period of time, and then adsorbed in the dark.

9. The use of the Cu / Cu2S / Ti3C2 composite material according to claim 8 in the adsorption of multivalent iodine, characterized in that: The Cu / Cu2S / Ti3C2 composite material after dark adsorption is dried, dispersed in deionized water, illuminated for 2-3 hours, centrifuged, filtered, washed and dried, and then can be used again for multivalent iodine adsorption.

10. Use of the Cu / Cu2S / Ti3C2 composite material according to claim 8 in the adsorption of multivalent iodine, characterized in that: The amount of the Cu / Cu2S / Ti3C2 composite material added to the water body is 0.25-2 g·L -1 ; The illumination time is 1 to 2 h; The dark adsorption time is 2 to 12 h.

Citation Information

Cited By

  • Preparation method of In2S3-Cu-Cu2O ternary heterojunction catalyst

    CN121244239A

  • A method for preparing an In2S3-Cu-Cu2O ternary heterojunction catalyst

    CN121244239B